Benefits of manual lymphatic drainage in post-operative plastic surgery (Research, Society and Development, 2021)
The demand for plastic surgery grows considerably, the technique aims to model the normal structures of the body, the procedure is invasive and requires post-surgical preparation, with this, the modality of manual lymphatic drainage is necessary in order to assist in vascular changes and in local edema, being indicated in the acute phase of the postoperative period, performed through light movements. The objective of this research is to describe through existing literature the benefits of manual lymphatic drainage in the postoperative period of plastic surgery. This is a literature review, in order to build new contexts on the subject through other literature examined in online platforms, as an exclusion criterion articles that did not fit the year and research topic. In the search base, literature review studies were found, which portray the importance of manual lymphatic drainage in the postoperative period of plastic surgery, portraying an improvement in the condition of edema, peripheral circulation and alleviating the risks of complications after surgery, in addition, improving the mental health of the individual who underwent body plastic surgery. It is concluded that manual lymphatic drainage has numerous benefits applied in the postoperative period of plastic surgeries, it presents an improvement in the physiological system as a whole, for the repair of the injured tissue after the invasive procedure, requiring further studies related to the topic for the elaboration of safe and efficient protocols.